Auxin-Responsive R2R3-MYB Transcription Factors HcMYB1 and HcMYB2 Activate Volatile Biosynthesis in Hedychium coronarium Flowers - Ke, Yanguo; Abbas, Farhat; Zhou, Yiwei; Yu, Rangcai; Fan, Yanping (Frontiers in Plant Science, 2021)
Auxin, an important plant hormone, induces the biosynthesis of various secondary metabolites by modulating the expression of auxin-responsive genes. In the ornamental plant Hedychium coronarium, linalool and methyl benzoate are biosynthesized by the terpene synthase (TPS) HcTPS5 and the benzoic/salicylic acid methyltransferase (BSMT) HcBSMT2, respectively. However, the transcriptional regulation of this process remains unclear. Here, we identified and functionally characterized the R2R3-MYB transcription factors HcMYB1 and HcMYB2 in regulating the biosynthesis of these floral aroma compounds. HcMYB1 and HcMYB2 are specifically expressed in flowers, their expression is correlated with the emission of volatile compounds in flowers, and is induced by auxin. Moreover, HcMYB1 and HcMYB2 interact with the HcBSMT2 promoter region. HcMYB2 activates the expression of the linalool synthase gene HcTPS5. In flowers with HcMYB1 or HcMYB2 silenced, the levels of floral scent compounds were significantly reduced, and HcBSMT2 and HcTPS5 were downregulated compared with the wild type. Moreover, HcMYB1 form protein-protein interaction with key scent-related HcIAA4 protein to regulate floral aroma production. Taken together, these results indicate that HcMYB1 and HcMYB2 play crucial roles in regulating the formation of scent compounds in H. coronarium flowers in response to auxin signaling.